Urban Planning in Remote, Extreme Environments - Hudgins, Ethan (2019)
Remote, extreme settlements often depend on an equally extreme dedication of resources and planning to achieve their goals, whether geopolitical, scientific, extractive or otherwise. This thesis uncovered pitfalls of these settlements, adding to the existing literature through a critical analysis of McMurdo Station, Antarctica. McMurdo exists as the logistical hub for the U.S. Antarctic Program, supporting the science activities on the continent. The remoteness and severity of the environment, combined with the numerous, well-documented failures of planning, have resulted in an operationally inefficient and substantially improvable station. This study adopts a mixed methods approach unique among planning methodologies, incorporating interviews of involved planners, scientists, and analysts, available planning documents and literature, and a Building Information Model (BIM) to qualitatively and empirically analyze the station planning and resulting design. This study found that remote, extreme settlements must critically balance their budgets, personnel, and resources in order to engender effective, contextual, local planning practices necessary to respond to the needs of the settlement. In the case of McMurdo, competing budget elements took priority over sustained planning efforts, capital investment and maintenance of the station, all of which contributed to a substantial breakdown between planning and station development. Additionally, the resulting cascade of planning failures evident at McMurdo suggests extreme settlements are a form of urbanism subject to the same planning needs and failures of more standard subjects of urban planning.